Enhancing hospital safety: The impact of resilience on safety climate, safety performance, and occupational accidents - Hamed Aghaei; Taleb Askaripoor; Morteza Siadat; Elahe Saleh (PLoS ONE, 2025)
This study examined the impact of individual and organizational resilience on safety climate, safety performance, and the incidence of occupational accidents among hospital employees in Iran. The research aimed to determine whether resilience, at both individual and organizational levels, enhances safety climate and performance, thereby reducing occupational accidents. This cross-sectional study was conducted in 2024, involving 343 administrative and patient care staff from four government hospitals in Semnan, Iran. Validated questionnaires were used to collect the data. Structural equation modeling analyzed the relationships among the variables. The findings revealed that individual and organizational resilience positively influenced safety climate and performance, resulting in a reduction in occupational accidents. Personal competence emerged as the strongest indicator of individual resilience, while adaptive resilience significantly impacted organizational resilience. Safety climate was found to mediate the relationship between resilience and safety performance, underscoring its critical role in enhancing safety outcomes. This study emphasizes the importance of fostering both individual and organizational resilience to improve safety climate and performance in healthcare settings. Interventions focused on resilience and a positive safety climate are essential for reducing occupational accidents, especially in high-stress environments like hospitals.